Determination of Triacylglycerols by HTGC-FID as a Sensitive Tool for the Identification of Rapeseed and Olive Oil Adulteration - Ying Qian; Magdalena Rudzińska; Anna Grygier; Roman Przybylski (Molecules, 2020)
Triacylglycerols (TGs) are the most common compounds in food lipids, accounting for 95% of the weight of edible oils. The aim of this study was to scrutinize a procedure for quantitatively assessing possible adulteration of olive and rapeseed oil through GC-FID analysis of TGs. The recovery of TG standards ranged from 21% to 148%, and the relative response factor (RRF) ranged from 0.42 to 2.28. The limits of detection were in the range of 0.001 to 0.330 µg/mL, and the limits of quantitation from 0.001 to 1.000 µg/mL. The validated method was used to determine the TGs in olive oil (OO), refined rapeseed oil (RRO), and their blends. Eight TGs were detected in refined rapeseed oil, and 10 in olive oil. The addition of 1% of olive oil to rapeseed oil or vice versa can be detected using this method. Three triacylglycerols were pinpointed as indicators of adulteration of rapeseed oil with olive oil (PPO, PPL, PSO). The method described here can be used for controlling the quality of these oils.